Effect of the Preheating Temperature on Process Time in Friction Stir Welding of Al 6061-T6 - Masoud Jabbari (Journal of Engineering)
This paper presents the results obtained and the deductions made from an analytical modeling involving friction stir welding of Al 6061-T6. A new database was developed to simulate the contact temperature between the tool and the workpiece. A second-order equation is proposed for simulating the temperature in the contact boundary and the thermal history during the plunge phase. The effect of the preheating temperature on the process time was investigated with the proposed model. The results show that an increase of the preheating time leads to a decrease in the process time up to the plunge and the preheating stage. Results of modeling the thermal history showed acceptable agreement with corresponding experimental data from the literature.